A STUDY OF RELIGIOUS ISSUES INORHAN PAMUK’S THE WHITE CASTLE - Umar Mushtaq (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Abstract: The present paper delves into the deep-seated conundrums about faith and secularist activities in Turkey that are prominently displayed Pamuk’s narrative. It also discusses Pamuk's depiction of the dominant value system, moral norms and religious standards in modern Turkey and the Ottoman Empire. The protagonist constantly find himself in unpleasant and perplexing circumstances due to the ongoing battle to define his religious identity. The clash between secularist values and religious fanaticism remains a contentious issue in contemporary Turkey.